Vitamin D Physiology, Deficiency, Genetic Influence, and the Effects of Daily vs. Bolus Doses of Vitamin D on Overall Health: A Clinical Approach - Vincenzo Sorrenti; Alessandro Buriani; Sergio Davinelli; Giovanni Scapagnini; Stefano Fortinguerra (Nutraceuticals, 2023)
Vitamin D is a pleiotropic hormone that plays a vital role in regulating bone growth, maintaining calcium and phosphate homeostasis, modulating immune function, and a wide range of other pleiotrophic actions in humans, which have increased the attention for its clinical applications. Despite its importance, vitamin D deficiency is prevalent worldwide and is related to a range of pathophysiological conditions, including an increased risk of osteoporosis and chronic and autoimmune diseases. The recommended daily doses of vitamin D vary depending on genetics, age, sex, and health status, with specific doses recommended for infants, children, adults, and those at increased risk of deficiency or specific health conditions. Maintaining adequate vitamin D levels is essential for optimal health, and together with sun exposure, appropriate supplementation strategies can help achieve this goal. Vitamin D supplementation is commonly used to maintain adequate levels, and the optimal administration strategy, such as a daily dose vs. a bolus, is still being investigated. This review aims to understand vitamin D physiology and the impact of relevant vitamin D polymorphisms and to evaluate the role of a daily dose versus a bolus in maintaining optimal vitamin D levels and clinical health outcomes. It also provides suggested clinical guidelines for clinicians based on the most recent scientific evidence.